Temporal variation and ecological parameters of hawkmoths (Lepidoptera: Sphingidae) in savannahs in the Alter do Chão protection area, Santarém, Pará, Brazil - Conceição, Ana Carla Walfredo da; Teston, José Augusto (Acta Scientiarum. Biological Sciences, 2020)
This study evaluated the seasonality of Sphingidae spp. in two areas of savannah, in the eastern Brazilian Amazon, sampled for one year (June, 2014 through May, 2015) with the aid of Pennsylvania light traps placed at four sampling points. Data on fauna were obtained through the following parameters: abundance (N), richness (S), composition, Shannon diversity and uniformity indices (H’ and U’), and the Berger-Parker (BP) dominance index. Richness estimates were calculated using Bootstrap, Chao1, ACE, Jackknife 1, and Jackknife2 estimators. The Pearson correlation was also used to analyze the effect of climatic variables such as rainfall, temperature, and relative humidity on richness and abundance. The result for the parameters analyzed during the entire sampling period was N= 374, S= 34, H’= 2.59, U= 0.733 and BP= 0.235. The estimation of richness showed that between 63% and 87% of expected species were collected (Bootstrap estimated 39 species and Chao1 estimated 54). The most representative species were: Isognathus caricae (Linnaeus, 1758) (N= 88), Enyo lugubris lugubris (Linnaeus, 1771) (N= 58), Isognathus menechus (Boisduval, [1875]) (N= 46) and Cocytius duponchel (Poey, 1832) (N= 44), with 54% of the sample containing species considered rare divided into 298 male and 76 female specimens. For climatic variables, there was a moderate positive correlation only between abundance and temperature. The less-rainy period presented greater richness (S= 26) and abundance (N= 222), and the rainy period had better indices for H’ (2.55), U (8.01), and BP (0.230). The richness estimator Jackknife 2 was the best estimator in both sampling periods with 34 in the less-rainy period and 45 in the rainy period. The richness and abundance obtained in this study contribute significantly to the knowledge of Sphingidae fauna in an area of Amazonian savannahs.